PENGARUH KOMITE AUDIT, KOMISARIS INDEPENDEN DAN STRUKTUR KEPEMILIKAN TERHADAP INTEGRITAS LAPORAN KEUANGAN: Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Kimia - Evi Dora Sembiring; Muhammad Angga Anggriawan; Sari Putri Pertiwi (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to analyze the effect of the audit committee, independent commissioners and ownership structure on the integrity of financial statements. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the chemical sub-sector for the period 2018-2021. The data used in this study is secondary data, which comes from the annual report. The sampling technique used is purposive sampling with the number of companies as many as 12 times 4 periods to 48 sample data. Methods of data analysis using SPSS version 26 program, namely descriptive statistics, classical assumption test and multiple regression analysis. The results of this study indicate that partially the audit committee has a positive effect on the integrity of the financial statements, the Independent Commissioner has a negative effect on the integrity of the financial statements. The ownership structure has no effect on the integrity of the financial statements. Meanwhile, simultaneously, the audit committee, independent commissioner and ownership structure affect the integrity of the financial statements